Processi di traduzione e scrittura elementare nella lingua straniera tedesca - Hoffmann, Sabine (Linguistica (Ljubljana), 2014)
The article presents the first results of a qualitative research study on writing in a foreign language with the help of Google Translator. It examines the processes of the construction of verbal and discursive forms during group discussion on the translation of a tourist website structures ensuing from a tourist website const. This study took place in the 2013/2014 academic year, and it was based on a video recording of about 12 hours of group work by 16 students while planning and producing a draft of the German translation of the homepage of an Italian tourist site. This study highlights both the advantages and disadvantages of the use of an online translation resource by students with basic knowledge of a foreign language.
Keywords: allemand; expression écrite; German; Googlov prevajalnik; moteur de traduction automatique Google; nemščina; pisno izražanje; prevajanje; traduction; translation; tuji jeziki